Enabling Better Nutrition for Adolescents from Middle Eastern Backgrounds: Semi-Structured Interviews with Parents - Nematullah Hayba (MDPI AG, 2021)
The unyielding obesity epidemic in adolescents from Middle Eastern (ME) backgrounds warrants culturally-responsive and co-designed prevention measures. This study aimed to capture the opinions of ME parents residing in Australia on the crisis and their enablers and barriers to healthy eating interventions given their influence on adolescent eating behaviors. Twenty-six semi-structured interviews were conducted with ME mothers, aged 35–59 years, and most residing in low socioeconomic areas (n = 19). A reflexive thematic analysis using the Capability, Opportunity, Motivation-Behaviour model and Theoretical Domain Framework was conducted. Parents expressed confidence in knowledge of importance of healthy eating, but were reluctant to believe behaviours were engaged in outside of parental influence. Time management skills are needed to support working mothers and to minimize reliance on nearby fast-food outlets, which was heightened during COVID-19 with home-delivery. Time constraints also meant breakfast skipping was common. A culture of feeding in light of diet acculturation and intergenerational trauma in this diaspora was also acknowledged. Parents pleaded for upstream policy changes across government and school bodies to support parental efforts in the form of increased regulation of fast-food and subsidization of healthy products. Opportunities for weight-inclusive programs including parenting workshops underpinned by culturally-responsive pedagogy were recommended.